The middle voice and the century - Valderrama, Miguel (Re-presentaciones: Periodismo, comunicación y sociedad, 2019)
This article presents a first outline on the relations between the middle voice and the century that staged it as a novelty or an archaic repetition. The middle voice has the trace of a dispute in historiography. It announces an alteration or interruption in the modern regime of historical representation. At least, it seems to be clear from the use of this expression by philosophers, historians and semiologists in debates about the writing of history. I would like to stablish in this essay, that the middle voice can be considered the “object of the century”, or better still the “thing” or “cause” on which the twentieth century seems to be based on